A comparative reading of pan-Africanism and Afropolitanism : come back Babar - Nyongesa, Andrew Wafula, 1980-; Mugubi, John (New York, NY : Routledge, 2024)
"This book is response to the recent surge of formidable voices that consistently demean and attempt to reverse the gains of pan-Africanism. Besides questioning its relevance, these voices supplant essential tenets of pan-Africanism - Blackness, the narrative of Return, sanctity of the ancestral homeland, exposition of evils of colonialism and African Literature - with new postulations. These new suppositions deny race, accentuate onward migration, and diminish the ancestral homeland to any ordinary city to globetrot. These voices liken any reminiscence of colonial evils to Afro-pessimism, pronounce African Literature dead on arrival and proceed to 'substitute' pan-Africanism through studies , which neglect pioneer and contemporary literary works, cultural productions, folklore, conversations on social media (blogs, Facebook, Whatapp) and questionnaires to gauge their influence among Black people themselves. This study adopts a design that interrogates literary works, data from questionnaires and social media to determine the relevance and influence of pan-Africanism and the new paradigm"--
Relevance of primordial identities: pan-Africanism in the face of globalisation -- Come back Babar: the place of pan-Africanism in Black literatures -- Frivolity of race: Afropolitanism and validity of class in contemporary literature and folklore -- Explicating ideological constructs within cinematic critique paradigm: a nexus to Afropolitanism and pan-African perspectives -- Conclusions, summaries and research findings.
Keywords: Pan-Africanism in literature; African diaspora in literature; LITERARY CRITICISM / African